STUDENTS’ ABILITY IN UNDERSTANDING HOMOPHONE IN ENGLISH - Adha, Ruly; Astri, Aprilisa (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
This research was aimed at finding out the ability of students to understand homophone in English. The research was qualitative descriptive research. The subject of the research was the seventh-semester students of the English Department of IAIN Langsa, academic year 2018/2019, that consisted of 32 students. The researchers used documentation as an instrument for collecting the data. The documentation was the result of the test given by a lecturer. The test given by the lecturer consisted of 20 questions about homophone in English. The question was in the form of phonetic transcription. The question consisted of two parts. In the first part, the students must mention two different words from a homophony sound. In the second part, the students must fill in the blank with a correct homophone word by relating to the pronunciation at the end of sentences. After conducting the research, the researchers found that 24 students got low mark because they were only able to answer one until ten questions correctly; 2 students got medium mark because they only answered 11 questions correctly, and six students got high mark because they can answer 12 until 17 questions correctly. Therefore, it can be said that the ability of students to understand homophone in English was not good enough. The problem faced by the students was that they still did not comprehend the concept of homophone in English. As a result of the test given by a lecturer, some students only knew that a homophone consisted of only one word, so they answered only one word, and some students also answered the question with three different words.